DARE Algorithm: A New Security Protocol by Integration of Different Cryptographic Techniques - John Mark Espalmado; Edwin Arboleda (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Exchange of information between computer networks requires a secure communications channel to prevent and monitor unauthorized access, modification and denial of the computer network. To address this growing problem, security experts sought ways to advance the integrity of data transmission. Security Attacks compromises the security and hence hybrid cryptographic algorithms have been proposed to achieve safe service in the proper manner, such as user authentication and data confidentiality. Data security and authenticity are achieved using these algorithms. Moreover, to improve the strength and cover each algorithm’s weaknesses, a new security algorithm can be designed using the combination of different cryptographic techniques. This design uses Digital Signature Algorithm (DSA) for authentic key generation, Data Encryption Standard (DES) for key scheduling, and Advanced Encryption Standard (AES) and Rivest–Schamir–Adleman Algorithm (RSA) in encrypting data. This new security algorithm has been proposed for improved security and integrity by integration of these cryptographic techniques.